2012
DOI: 10.1172/jci58431
|View full text |Cite
|
Sign up to set email alerts
|

FOSL2 promotes leptin gene expression in human and mouse adipocytes

Abstract: The adipocyte-derived hormone leptin is a critical regulator of many physiological functions, ranging from satiety to immunity. Surprisingly, very little is known about the transcriptional pathways that regulate adipocyte-specific expression of leptin. Here, we report studies in which we pursued a strategy integrating BAC transgenic reporter mice, reporter assays, and chromatin state mapping to locate an adipocyte-specific cis-element upstream of the leptin (LEP) gene in human fat cells. Quantitative proteomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 62 publications
4
57
0
3
Order By: Relevance
“…ChIP-seq analysis for C/EBP and AP-1 factors that are abundant in adipocytes revealed significant enrichment at down-regulated eRNAs of both C/EBPa and FOSL2 (Fig. 5B), which has been shown to play a role in adipocyte gene expression (Wrann et al 2012). A higher percentage of downregulated eRNAs, compared with up-regulated and nonregulated, had C/EBPa and FOSL2 bound, and, interestingly, although C/EBPa has been shown to be enriched near genes repressed after rosi treatment (Vernochet et al 2009;Haakonsson et al 2013), the enrichment was The closest known motif, the DR1 motif, is shown for reference.…”
Section: Repression Of Erna Transcription By Rosi Is Not Directly Medmentioning
confidence: 99%
“…ChIP-seq analysis for C/EBP and AP-1 factors that are abundant in adipocytes revealed significant enrichment at down-regulated eRNAs of both C/EBPa and FOSL2 (Fig. 5B), which has been shown to play a role in adipocyte gene expression (Wrann et al 2012). A higher percentage of downregulated eRNAs, compared with up-regulated and nonregulated, had C/EBPa and FOSL2 bound, and, interestingly, although C/EBPa has been shown to be enriched near genes repressed after rosi treatment (Vernochet et al 2009;Haakonsson et al 2013), the enrichment was The closest known motif, the DR1 motif, is shown for reference.…”
Section: Repression Of Erna Transcription By Rosi Is Not Directly Medmentioning
confidence: 99%
“…Thus, mice overexpressing Fra-2 develop an osteosclerotic phenotype, whereas the absence of Fra-2 leads to a defect of osteoblast differentiation 15 and a giant osteoclast phenotype induced by the activation of HIF1a. 16 Furthermore, leptin is a transcriptional target of Fra-2, 17 suggesting that Fra-2 may indeed represent an important transcription factor for adipocytes. Herein, we show that Fra-2 deletion in adipocytes affects body and fat pad mass by the regulation of adipocyte number.…”
mentioning
confidence: 99%
“…Distinct target genes are regulated by the Fos-related proteins Fra-1 and Fra-2, which control osteoblast differentiation and activity, rather than osteoblast numbers (Bozec et al, 2010;Eferl et al, 2004). Fra-2 transcriptionally regulates leptin, which can control energy homeostasis in mesenchymal cells (Wrann et al, 2012). Surprisingly, leptin was not affected in Fra-2 mutant mice, whereas the levels of the adipokine Adipoq were found to be altered in Fra-2 mutant sera.…”
Section: Discussionmentioning
confidence: 97%
“…Fra-2 expression in osteoblasts controls Adipoq production Fra-2 was recently shown to control leptin expression in adipocytes (Wrann et al, 2012). We therefore measured the levels of serum adipokines and Ocn isoforms in Fra-2 mutant mice.…”
Section: Osteoblast-specific Fra-2 Expression Affects Bone Formation mentioning
confidence: 99%